Toward a new energy paradigm in geography: revisiting the curriculum and teaching practices - MAŽEIKIENĖ, NATALIJA; Norkutė, Odeta (Journal of Education Culture and Society, 2021)
Aim. The aim of the article is to investigate how energy topics are presented in the geography curriculum in Lithuania and how school geography becomes an educational response to the current global challenges related to energy production and consumption. Methods. The article presents research using several methods: review of literature on energy geography and energy literacy, analysis of Lithuanian national curriculum for geography, content analysis of 14 geography textbooks for forms 6–12, expert interview with 9 geography teachers. Results. The empirical research reveals that the national curriculum and textbooks still represent the old energy paradigm with a profound focus on fossil fuel and nuclear energy resources. Meanwhile, the new energy paradigm is realised in the teaching of experienced and qualified teachers who, in addition to the new green energy economy, emphasise environmental and social issues of energy use. Conclusions. The conclusions include observations on necessary changes in teaching energy geography: on the one hand, by revising the formal curriculum and textbooks and integrating concepts of energy literature and new energy developments; on the other hand, by initiating changes in primary and continuous teacher education. Professional development of teachers could include new energy topics, new teaching and learning sources (political debates in media, TV, strategic energy development documents), new teaching and learning strategies and methods.